2014
DOI: 10.4049/jimmunol.1401081
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic IgG Antibodies against Desmoglein 3 in Pemphigus Vulgaris Are Regulated by HLA-DRB1*04:02–Restricted T Cells

Abstract: Pemphigus vulgaris (PV) is considered as a model for an autoantibody-mediated organ-specific autoimmune disorder. IgG autoantibodies directed against the desmosomal cadherin desmoglein 3 (Dsg3), the major autoantigen in PV, cause loss of epidermal keratinocyte adhesion, resulting in blisters and erosions of the skin and mucous membranes. The association of human autoimmune diseases with distinct HLA alleles is a well-known phenomenon, such as the association with HLA-DRB1*04:02 in PV. However, direct evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 58 publications
1
65
0
4
Order By: Relevance
“…5b). Another approach is a mouse model with a MHC class II-null background that expresses the pemphigus-associated HLA-DRB1*0402 allele 109 (FIG. 5c).…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…5b). Another approach is a mouse model with a MHC class II-null background that expresses the pemphigus-associated HLA-DRB1*0402 allele 109 (FIG. 5c).…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Analysis of the peptides that these Dsg3-specific T cells recognize showed that they derive mostly from the amino-terminal extracellular domain of Dsg3 and share anchor residues at relative positions 1, 4, and 6 (position 4 being positively charged and critical for binding to the negatively charged p4 binding pocket of DRB1*0402) (74). The relevance of the restriction of the Dsg3-specific CD4+ T cell response to HLA-DRB1*0402 for human disease pathophysiology was demonstrated in vivo by immunization of mice transgenic for HLA-DRB1*0402 with such peptides, in which case anti-Dsg3 pathogenic antibodies were produced; however, such peptides do not produce autoantibodies in HLA-DRB1*0401-transgenic mice, and Dsg3 peptides that do not bind the HLA-DRB1*0402 pocket also do not produce autoantibodies in HLA-DRB1*0402-transgenic mice (75). Finally, CD4+CD25+ regulatory T cells have been implicated in maintaining peripheral tolerance to Dsg3 in mice, and in healthy human carriers of the PV-associated HLA-DRB1*0402 and DQB1*0503 alleles, through the suppression of CD4+ effector T cells (76, 77).…”
Section: Pemphigus Pathophysiologymentioning
confidence: 99%
“…Using a humanized HLA-DRB1*04:02 transgenic mouse model, it was recently shown that T cell recognition of Dsg3 is tightly associated with the HLA-DRB1*04:02 transgene. Additionally, it was shown that T cell–dependent B cell activation was critical for the induction of pathogenic IgG antibodies (34). However, as correctly stated by the authors, this mouse model is only suitable for investigating the effector phase of the autoimmune response in PV.…”
Section: Pv Desmoglein 3 and Hla-drb1*0402mentioning
confidence: 99%
“…However, in the absence of T cells there was no detectable autoantibody production by B cells (38), suggesting that T cells are necessary for the anti-Dsg3 antibody production by B cells. Indeed, recent in vitro and in vivo studies have shown that an interaction between T cells and B cells was necessary for autoantibody production in PV (34, 39). In addition, Dsg3-specific T cells have been shown to be present at higher levels in the peripheral blood of PV patients compared to healthy controls (40).…”
Section: Pv Desmoglein 3 and Hla-drb1*0402mentioning
confidence: 99%